2015
DOI: 10.1039/c5ra19104a
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of PEG coated nanoscale gold particles for enhanced radiation therapy

Abstract: To enhance PEG uptake for radiation therapy, a peptide containing an integrin binding domain (RGD) was conjugated to PEG. Nanoparticles functionalized with both the RGD peptide and PEG had a higher uptake than NPs functionalized with PEG alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(44 citation statements)
references
References 38 publications
3
40
0
1
Order By: Relevance
“…The nanoparticles appear bright as a consequence of their high scattering cross section, thus allowing the optical detection of small nanoparticles clusters or even individual ones. It has been recently shown that gold nanoparticles have unique reflectance spectra presenting well-defined peaks located between 550 and 650 nm [18]. By examining the reflectance spectra acquired on the most dominant three classes of nanoparticles detected in the field of view (green, red, and orange), one can observe that each of these spectra presents a well-defined peak located between 550 and 650 nm ( Figure 5(b)).…”
Section: Resultsmentioning
confidence: 92%
“…The nanoparticles appear bright as a consequence of their high scattering cross section, thus allowing the optical detection of small nanoparticles clusters or even individual ones. It has been recently shown that gold nanoparticles have unique reflectance spectra presenting well-defined peaks located between 550 and 650 nm [18]. By examining the reflectance spectra acquired on the most dominant three classes of nanoparticles detected in the field of view (green, red, and orange), one can observe that each of these spectra presents a well-defined peak located between 550 and 650 nm ( Figure 5(b)).…”
Section: Resultsmentioning
confidence: 92%
“…For example, the gold (Z = 79) has much stronger photoelectric effect than that of soft tissues (average Z = 7.4). [31][32][33][34][35][36][37][38][39] Au loaded polymeric nanocapsules [40][41][42][43] Au nanomolecules [40,44,45] Active targeting Au nanoparticles [44,[46][47][48][49][50] Rare earth element Gadolinium oxide; Gd doped carbon dots; Gd doped calcium phosphate [51][52][53][54] Upconversion nanoparticles (e.g. Such electron rearrangement in atom orbits would generate excess energy that released either as fluorescent photons or Auger electrons, the latter of which traveling through much shorter distances (typically ≈10 nm) are able to produce high ionization effects in local areas.…”
Section: Mechanisms Of Radio-sensitization With High-z Elementsmentioning
confidence: 99%
“…A Summary of nanomaterials for enhancing EBRT. Element Materials References Gold Au nanoparticles/nanorods/nanoshells [31][32][33][34][35][36][37][38][39] Au loaded polymeric nanocapsules [40][41][42][43] Au nanomolecules [40,44,45] Active targeting Au nanoparticles [44,[46][47][48][49][50] Rare earth element Gadolinium oxide; Gd doped carbon dots; Gd doped calcium phosphate [51][52][53][54] Upconversion nanoparticles (e.g.NaYbF 4 [82][83][84] Pt nanoparticles [85,86] Ag nanoparticles; Fe 3 O 4/ Ag nanocomposite [87][88][89][90][91] Non high-Z elements Iron oxide nanoparticles [92][93][94] TiO 2 nanoparticles/nanotubes [95,96] Si nanoparticles [97,98] www.advmat.de www.advancedsciencenews.com (1.9 nm) -loaded polymeric micelles that exhibited longer blood circulation and 6-fold increase in tumor uptake, compared to that of ultrasmall Au nanoparticles...…”
Section: Doi: 101002/adma201700996mentioning
confidence: 99%
“…Although most studies suggest that deoxyribonucleic acid (DNA) is damaged indirectly by hydroxyl radicals, electrons can also cause damage to DNA directly (Boudaıffa et al 2000). Recent in vitro and in vivo studies have shown that the incorporation of GNPs into current radiotherapy protocols produces better outcomes at clinically relevant megavoltage energies (Cruje et al 2015;Wolfe et al 2015). Intravenously injected NPs can accumulate within the tumor using its leaky vasculature, penetrate through the tumor tissue and finally enter the individual tumor cells (Abolfazli et al 2015;Yang et al 2018).…”
Section: Introductionmentioning
confidence: 99%